Influence of cobalt substitution in CoFe2O4 nanoparticles on structural, morphological, cation distribution, optical and magnetic properties - Z. Mosleh; M. Beygmohammadvand; A. Ghotbi Varzaneh; P. Kameli (Heliyon)
This paper presents the first-time synthesis of CoFe2−xCoxO4 nanoparticles (where x = 0.0, 0.1, 0.2, 0.3, 0.4, 0.5, and 0.6) through hydrothermal methods utilizing metal chloride precursors. X-ray diffraction (XRD) analysis confirms the formation of a cubic spinel structure characterized by the Fd3¯m space group. Field Emission Scanning Electron Microscopy (FE-SEM) images reveal that the average grain size of the nanoparticles lies between 50 nm and 90 nm. Notably, the optical band gap of the Co3+-doped samples exhibits a gradual increase from 1.7 eV to 2.5 eV. Furthermore, a reduction in saturation magnetization was noted with increasing doping content at both 5 K and 300 K. The observed decrease in saturation magnetization in the doped samples can be attributed to the migration of Co2+ ions from the B site to the A site, as well as the substitution of Fe3+ ions with Co3+ ions in the B site. Additionally, the influence of annealing temperature on the structure, morphology, and magnetic properties of the nanoparticles was examined.